Kesiapan dan Penerimaan Karyawan terhadap Penerapan Lean Management di Rumah Sakit Bethesda - Katherina Adisaputro; Andreasta Meliala (Jurnal Manajemen Kesehatan Indonesia, 2021)
ABSTRACTIntroductions: Efficiency of health care services at a hospital became one of the solutions amid national health insurance era. Particular method offering the solution is lean management. Bethesda Hospital began implementing lean management in 2019. During the course of the program, readiness and acceptance evaluation at the level of employee never been accomplished. Organizations focused mainly on lean tools and lean techniques tend to allocate minimal measurement on readiness lead to reduced level of sustainability and last for short-term activities. Successful lean management require both preparation and implementation combining on lean readiness and lean acceptance data from the organization. Aim:This study aimed to measure employee readiness and acceptance toward implementation of lean management,and to describe the output of lean implementationMethods: An explanatory research took place in Bethesda Hospital, Yogyakarta. Survey were used to collect quantitative data while the qualitative approach performed through in-depth interviews.Results and Discussion: Lean readiness at Bethesda Hospital were analyzed using fuzzy and Euclidean. The analysis indicate value of 6.08 with HLR 4 distance 2.016 interpreted as "close to ready", therefore Bethesda Hospital is ready to start the lean journey, but is not yet fully ready , as well as continuous improvement.The aspects of readiness that still lack of improvement include supplier and customer involvement in lean, lean sensei in institutions, employee resistance, and reward systems.The highest indicator identified from element 6.4, patient and employee safety, while the lowest indicator originated from element 5.2, supplier involvement and conformity to the institution. Lean acceptance Bethesda Hospital measured through lean maturity present average score level 3, but in operational conditions at the hospital lean maturity is at level 2 where awareness of lean has occurred in general, but the lean approach only occurs in some areas with variability of effectiveness. The aspects of lean that still lack of improvement is the foundation of lean philosophy and a monitoring evaluation system that has not been standardized in all of sections.Conclusion: The lean implementation that has been carried out has provided good output in both financial and non-financial term. Bethesda hospital is considered to have the ability to start a lean journey, but the aspects of readiness that are lacking need to be improved. Bethesda hospital has sufficient level of acceptance to undertake further development of lean implementation.